Source code reviews on mobile devices - Frącz, Wojciech; Dajda, Jacek (Computer Science, 2016)
This paper presents the results of an experiment-driven investigation on the efficiency of source code review practice performed on mobile devices. In particular, the conducted investigation tries to verify whether or not the small screens of mobile devices influence the speed and quality of the review process. Besides presenting the experiment itself and discussing the obtained results, this paper also describes the dedicated Android application for mobile code reviews that was implemented for research purposes.